Developing and evaluating Birthing on Country services for First Nations Australians: the Building On Our Strengths (BOOSt) prospective mixed methods birth cohort study protocol - Penny Haora; Yvette Roe; Sophie Hickey; Yu Gao; Carmel Nelson; Jyai Allen; Melanie Briggs; Faye Worner; Sue Kruske; Kristie Watego; Sarah-Jade Maidment; Donna Hartz; et al. (BMC, 2023)
Abstract Background With the impact of over two centuries of colonisation in Australia, First Nations families experience a disproportionate burden of adverse pregnancy and birthing outcomes. First Nations mothers are 3-5 times more likely than other mothers to experience maternal mortality; babies are 2-3 times more likely to be born preterm, low birth weight or not to survive their first year. 'Birthing on Country' incorporates a multiplicity of interpretations but conveys a resumption of maternity services in First Nations Communities with Community governance for the best start to life. Redesigned services offer women and families integrated, holistic care, including carer continuity from primary through tertiary services; services coordination and quality care including safe and supportive spaces. The overall aim of Building On Our Strengths (BOOSt) is to facilitate and assess Birthing on Country expansion into two settings - urban and rural; with scale-up to include First Nations-operated birth centres. This study will build on our team's earlier work - a Birthing on Country service established and evaluated in an urban setting, that reported significant perinatal (and organisational) benefits, including a 37% reduction in preterm births, among other improvements. Methods Using community-based, participatory action research, we will collaborate to develop, implement and evaluate new Birthing on Country care models. We will conduct a mixed-methods, prospective birth cohort study in two settings, comparing outcomes for women having First Nations babies with historical controls. Our analysis of feasibility, acceptability, clinical and cultural safety, effectiveness and cost, will use data including (i) women's experiences collected through longitudinal surveys (three timepoints) and yarning interviews; (ii) clinical records; (iii) staff and stakeholder views and experiences; (iv) field notes and meeting minutes; and (v) costs data. The study includes a process, impact and outcome evaluation of this complex health services innovation. Discussion Birthing on Country applies First Nations governance and cultural safety strategies to support optimum maternal, infant, and family health and wellbeing. Women's experiences, perinatal outcomes, costs and other operational implications will be reported for Communities, service providers, policy advisors, and for future scale-up. Trial registration Australia & New Zealand Clinical Trial Registry # ACTRN12620000874910 (2 September 2020).